Notched noise reveals differential improvement in the neural representation of the sound envelope - Amarins N. Heeringa; Jonas Klug; Christine Köppl; Mathias Dietz (Communications Biology)
Abstract Precise temporal coding in auditory nerve fibers is crucial for sound localization and listening in noise. However, at higher sound levels, typical of everyday listening situations, temporal coding to the stimulus envelope is poor in fibers of the on-frequency channel, i.e., those tuned to the carrier stimulus. We predict that changes in cochlear gain improve temporal coding of the stimulus envelope differentially across frequency channels. Both auditory nerve fiber recordings (in Mongolian gerbils of either sex) and human psychophysics confirm that weak temporal coding at higher levels is improved when the target stimulus is presented in a spectrally flanking notched noise designed to reduce the cochlear gain. The proposed mechanism can help to explain the effect of cochlear gain loss, a known consequence of age- and noise-induced hearing loss, on everyday listening, such as problems with speech-in-noise perception and sound localization.